1
$\begingroup$

I was just playing around with the product rule of differentiation, and I followed some steps, which I think are authentic, but I am not able to explain the result.

Let $f:\mathbb{R}\to\mathbb{R}$ and $g:\mathbb{R}\to\mathbb{R}$ be two differentiable functions at every $x$. And let us suppose that we want to differentiate the function $p(x)=f(x)g(x)$ at some $x$. So, $$\begin{align}p'(x)&=\lim_{h\to0}\frac{p(x+h)-p(x)}{h}\\ &=\lim_{h\to0}\frac{f(x+h)g(x+h)-f(x)g(x)}{h}\\ \end{align}$$

For this particular case, lets assume that $f(x)\in\mathbb{R}/\{0\}$. So, factoring $f(x)$, we get: $$\begin{align} &=\lim_{h\to0}f(x)\left\{\frac{f(x+h)g(x+h)}{f(x)\dot{}h}-\frac{g(x)}{h}\right\} \end{align}$$ Now, all I am doing is using limit properties(addition, subtraction, multiplication): $$\begin{align} &=f(x)\lim_{h\to0}\left\{\frac{f(x+h)g(x+h)}{f(x)\dot{}h}-\frac{g(x)}{h}\right\}\\ &=f(x)\left\{\lim_{h\to0}\frac{f(x+h)g(x+h)}{f(x)\dot{}h}-\lim_{h\to0}\frac{g(x)}{h}\right\}\\ &= f(x)g'(x) \end{align}$$ To desribe as to how I computed the limits in the braces, I split the first limit as two functions, and used the fact that $\lim_{h\to0}\frac{f(x+h)}{f(x)}=1$. And for the rest, I combined the two limits, giving the derivative of $g$ at $x$. What is the problem in these steps? Initially, I assumed $f(x)\ne0$, so undefined is out of the view.

$\endgroup$
  • $\begingroup$ Using the same logics, you can even conclude $\lim f(x)g(x)\{f(x+h)g(x+h)/f(x)g(x)h-1/h\}=0$. $\endgroup$ – Yves Daoust Dec 7 '16 at 14:22
3
$\begingroup$

First, the splitting of the limit $$ \lim_{h\to0}\{\frac{f(x+h)g(x+h)}{f(x)\dot{}h}-\frac{g(x)}{h}\} = \{\lim_{h\to0}\frac{f(x+h)g(x+h)}{f(x)\dot{}h}-\lim_{h\to0}\frac{g(x)}{h}\} $$

is incorrect, as both limits on the right side do not exist generally (if $g(x) \neq 0$). That's easy to see, the enumerator of $\frac{f(x+h)g(x+h)}{f(x)\dot{}h}$ goes to $f(x)g(x)$, while the denominator goes to $0$. Similiarly, the enumarator of the second term is a constant $g(x)$, while the denominator goes to $0$.

What you did is similar to the following:

$$2 = \lim_{x \to 0} 2 = \lim_{x \to 0} \{(2+\frac{1}{x}) - \frac{1}{x} \} = \lim_{x \to 0} (2+\frac{1}{x}) - \lim_{x \to 0}\frac{1}{x} = \lim_{x \to 0} \frac{1+2x}{x} - \lim_{x \to 0}\frac{1}{x} = \lim_{x \to 0} \frac{1+2x}{1+x} \frac{1+x}{x}- \lim_{x \to 0}\frac{1}{x} = \lim_{x \to 0} \frac{1+x}{x} - \lim_{x \to 0}\frac{1}{x} = \lim_{x \to 0} (1+\frac{1}{x}) - \lim_{x \to 0}\frac{1}{x} = \lim_{x \to 0} \{(1+\frac{1}{x}) - \frac{1}{x} \} = 1$$

using the correct fact that $\lim_{x \to 0} \frac{1+2x}{1+x} = 1$

All those terms $\lim_{x \to 0}\frac{1}{x}$ are meaningless, as they are equal to $\infty$ and you cannot meaningfully subtract two infinities. As my equations shows, you can transform any finite term like 2 into another finite term like 1.

That's what happened to you when you rewrote the formula for differentiation of a product: You had some infinite terms in between, and "adjusted" one of them with a factor ($ \frac{f(x+h)}{f(x)}$) that goes to 1 under the limit (just as I did with the factor $\frac{1+2x}{1+x}$). But since that factor applied to a term that went to $\infty$ under the limit, you got the incorrect conclusion.

$\endgroup$
2
$\begingroup$

You can't split up the limit $\lim \limits_{h \to 0} \left\{\frac{f(x + h)g(x + h)}{f(x) h} - \frac{g(x)}{h}\right\}$ into two limits, since the two limits in general won't converge. The rule $$\lim \limits_{x \to x_0} (f(x) + g(x)) = \lim \limits_{x \to x_0} f(x) + \lim \limits_{x \to x_0} g(x)$$ can only be applied, if both the limits on the right-hand side exist.

$\endgroup$
0
$\begingroup$

The step where you split the limit in two is invalid. The second limit does not exist (goes to infinity for h to zero). So splitting the limit is not allowed to begin with.

$\endgroup$
0
$\begingroup$

$$\frac{f(x+h)}{f(x)}$$ does tend to $1$, and

$$\frac{f(x+h)}{f(x)}-1$$ does tend to $0$.

But this doesn't mean that

$$\frac1h\left(\frac{f(x+h)}{f(x)}-1\right)$$ tends to $0$. On the opposite, it tends to

$$\frac{f'(x)}{f(x)}.$$


When you subtract two terms having a constant and a variable part (the limit and a discrepancywhich is a function of $h$), if the constant parts cancel out, the variable part becomes the main contribution.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.